2006
DOI: 10.1007/s00701-006-0887-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of apoptosis in cerebrospinal fluid of patients with severe head injury

Abstract: This study indicates a prolonged activation of pro-apoptotic (sFas, caspase-3) and anti-apoptotic (bcl-2) proteins after severe TBI in humans. The degree of activation of particularly caspase-3 may be related to the severity of the injury. Parallel increases of these three molecules may indicate a pivotal role of apoptosis in the pathophysiology of post-traumatic brain oedema, secondary cell destruction and chronic cell loss following severe TBI and may open new targets for post-traumatic therapeutic intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 33 publications
1
40
0
Order By: Relevance
“…A larger study population with more frequent ␣ -synuclein sampling would be instrumental in accomplishing this. Finally, mitochondrial dysfunction, inclusive and exclusive of cytochrome c release, is also an important factor in secondary injury following TBI [Robertson et al, 2009;Uzan et al, 2006]. TH is a promising intervention protecting mitochondrial viability in animal models of ischemic injury [Canevari et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…A larger study population with more frequent ␣ -synuclein sampling would be instrumental in accomplishing this. Finally, mitochondrial dysfunction, inclusive and exclusive of cytochrome c release, is also an important factor in secondary injury following TBI [Robertson et al, 2009;Uzan et al, 2006]. TH is a promising intervention protecting mitochondrial viability in animal models of ischemic injury [Canevari et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…correlated with increased intracranial pressure. Soluble Fas and caspase-3 peaks coincided on day 5 after trauma, with significant association between soluble Fas and caspase-3 increase [9]. Data also showed that detection of markers of inflammation in the CSF of patients with TBI.…”
Section: Discussionmentioning
confidence: 63%
“…However, some of the proteins such as cystatin-C, alpha-1-antitrypsin and other housekeeping proteins are usually also detected in normal CSF and should not be regarded as to be related specifically to TBI. In order to assess how many potential biomarkers for TBI that could be detected with the HLL, a literature search was conducted and is summarized in Table 2 [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Only proteins reported to have a down/up-regulation in CSF or human brain tissue in relation to an inflicted trauma to the head are included in the table.…”
Section: Resultsmentioning
confidence: 99%